TRENDS IN THE DEVELOPMENT OF INTEGRATED MARKETING COMMUNICATION IN THE CONTEXT OF DIGITAL MARKETING - Bormane, Santa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Nowadays, in the context of digital marketing and social media development, with the advantages given by technologies and the vast possibilities of communication among consumers, businesses find the implementation of integrated marketing communication influenced by the Internet as a marketing communication environment where businesses are urged into a customer-centric approach by the consumers’ changing habits of receiving information. This results in an increased role of content marketing, relationship orientation, dialogue and network communication, management of multiple stakeholders etc., which envisages consumer involvement with a view to mitigating the consequences caused by the obstacles to marketing communication – loss of control over corporate communication and being adversely affected by invisible communication. Aim of the research was to study and assess integrated marketing communications in the context of digital marketing and its influence upon buyers’ buying decisions. The object of the research is integrated marketing communications. The subject of the research is the influence of integrated marketing communication upon buyers’ buying decisions. The research makes use of the results of studies conducted by the author in 2017 and 2018. There was a survey of leading marketing specialists of Latvian food retail chains and a survey of randomly selected buyers with a sample of 1,003 respondents to find out the influence of integrated marketing communications upon the buyers’ buying decisions. The research brings conclusions regarding the consumption habits of different generations and other factors influencing buying decisions. The research confirmed the hypothesis that integrated marketing communications in the context of digital marketing is a relatively little used type of communication in the marketing communication strategy of businesses, yet its use facilitates consumer loyalty. The results of the research are of both theoretical and practical value.